Students' Financial Management Behavior: Potential Factor And Understanding Of The Tri Pantangan Teachings - Erawati, Teguh; Muda Rondi, Kresensia (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2025)
Many students tend to be less aware of financial responsibility and the need to manage finances efficiently. This is often influenced by various factors, including the culture of debt and the consumer lifestyle that is common among today's teenagers. This research aims to examine the influence of financial attitudes and understanding of the teachings of the tri pantangan on Student Financial Management Behavior. The respondents of this research were 100 students of the Accounting Study Program at Bachelorwiyata Tamansiswa University. Data was collected through surveys using questionnaires, and data quality was analyzed through validity and reliability. Data analysis includes testing classical assumptions, normality, multicollinearity and heteroscedasticity. The hypothesis was tested using the T test, F test, and R2 test with the help of SPSS version 23 software. The research results showed that Financial Attitudes and Understanding of the Tri pantangan Teachings had a positive and significant effect on students' financial management behavior. Apart from that, these two factors also simultaneously have a positive and significant effect on students' financial management behavior.